Highly efficient and regioselective synthesis of spirooxindolo pyrrolizidines by reaction of isatin, proline and acrylonitrile/methyl acrylate in water. Issue 21 (25th May 2016) - Tiwari, Keshri Nath; Pandurang, Taur Prakash; Pant, Suyash; Kumar, Rahul
Graphical abstract: Abstract: A simple, ecofriendly and regioselective three-component condensation of nonstabilzed azomethine ylides generated in situ from isatins andl -proline with acrylonitrile/methyl acrylate to give spirooxindolo pyrrolizidines has been realized. The reaction highlights the use of water as a reaction medium with good to excellent yields of products from readily available precursors.